2013
DOI: 10.1177/0960327113512341
|View full text |Cite
|
Sign up to set email alerts
|

Vasorelaxant effects of mercury on rat thoracic aorta

Abstract: Mercury, a heavy metal, is widespread and persistent in the environment and has been elucidated as a possible risk factor in cardiovascular diseases. Mercury has been reported to selectively impair the nitric oxide (NO) pathway in the vascular endothelium as a consequence of oxidative stress. Conversely, mercury per se causes endothelium-dependent vasorelaxation at lower concentration via the NO pathway. Little is known about the effects of mercury per se on other endothelial mediators. To elucidate p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…7 nM (7). Unlike other studies where the effect of Hg(II) was seen on pre-contracted aortic segments, in this study we have compared the maximum contractile response of aortic segments that have been pre-incubated with As(III) and Hg(II) in the relevant concentration range (5). Optimum incubation time was found to be 40 min.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…7 nM (7). Unlike other studies where the effect of Hg(II) was seen on pre-contracted aortic segments, in this study we have compared the maximum contractile response of aortic segments that have been pre-incubated with As(III) and Hg(II) in the relevant concentration range (5). Optimum incubation time was found to be 40 min.…”
Section: Resultsmentioning
confidence: 99%
“…Mercury has also been reported to enhance contraction responses in aortic segments (7). A biphasic effect of mercury has recently been reported, with vasorelaxation at lower concentrations and vasoconstriction at higher concentrations in pre-contracted aortic segments (5). We did not observe biphasic responses in this study, possibly because we measured the tension after 40 min of Hg(II) incubation of the resting aortic segments which may lead to generation of ROS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wiggers et al used lower doses of mercury and showed a reduction in the participation of potassium channels in mesenteric resistance arteries. However, other authors have demonstrated that acute incubation with different concentrations of mercury can stimulate or suppress potassium efflux currents that are sensitive to TEA or glibenclamide in human B lymphocytes, proximal tubular cells of the frog kidney and rat thoracic aorta . Because endothelial NO can directly activate the potassium channels, especially BK Ca , and ROS can negatively modulate the activity of these channels, we evaluated the vasodilatation in response to the NO donor SNP after a pre‐incubation with tiron to test the response to a known amount NO without the influence of local ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Similar observations were reported by our group ascertaining that mercury exposure produces a biphasic response-vasorelaxation at lower concentrations and vasoconstriction at higher concentrations. 73 The ECs secrete oxygen-derived free radicals and H 2 O 2 in response to stress. 74 Superoxide anion inactivates NO, 69 resulting in vasoconstriction of arteries.…”
Section: Mercury Exposure Oxidative Stress and Vascular Endotheliummentioning
confidence: 99%